KORELASI ANTARA KONDISI SANITASI DASAR TERHADAP PENGETAHUAN SIKAP DAN PRILAKU SISWA SEKOLAH DASAR - Ardisal Ardisal; Markis Yunus (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
This research is a quantitative research whose purpose to find out the correlation between condition of basic sanitation and the elementary students ability with the use of basic sanitation means. Data collection is done by using test and quetioners. The data was analyzed by regression analysis. Suggestion in this study is to improve the infrastructure of basic sanitation and give information for elementary student about the use and the need of healthy live.